Clinical and molecular characterization of the 20q11.2 microdeletion syndrome: Six new patients. (8th January 2015) - Jedraszak, Guillaume; Demeer, Bénédicte; Mathieu‐Dramard, Michèle; Andrieux, Joris; Receveur, Aline; Weber, Astrid; Maye, Una; Foulds, Nicola; Temple, IK; Crolla, John; Alex‐Cordier, Marie‐Pierre; Sanlaville, Damien; et al.
<x xml:space="preserve">Abstract</x> Interstitial microdeletions of 20q chromosome are rare, only 17 patients have been reported in the literature to date. Among them, only six carried a proximal 20q11.21‐q11.23 deletion, with a size ranging from 2.6 to 6.8 Mb. The existence of a 20q11.2 microdeletion syndrome has been proposed, based on five previously reported cases that displayed anomalies of the extremities, intellectual disability, feeding difficulties, craniofacial dysmorphism and variable malformations. To further characterize this syndrome, we report on six new patients with 20q11.2 microdeletions diagnosed by whole‐genome array‐based comparative genomic hybridization. These patient reports more precisely refined the phenotype and narrowed the minimal critical region involved in this syndrome. Careful clinical assessment confirms the distinctive clinical phenotype. The craniofacial dysmorphism consists of high forehead, frontal bossing, enophthalmos, and midface hypoplasia. We have identified a 1.62 megabase minimal critical region involved in this syndrome encompassing three genes ‐ GDF5, EPB41L1, andSAMHD1– which are strong candidates for different aspects of the phenotype. These results support that 20q11.2 microdeletion syndrome is a new contiguous gene deletion syndrome with a recognizable phenotype. © 2015 Wiley Periodicals, Inc.